Gut microbiome: A potential indicator for predicting treatment outcomes in major depressive disorder - Dong, Zaiquan; Shen, Xiaoling; Hao, Yanni; Li, Jin; Xu, Haizhen; Yin, Li; Kuang, Weihong (Frontiers in Neuroscience, 2022)
The therapeutic outcomes in major depressive disorder (MDD), one of the most common and heterogeneous mental illnesses, are affected by factors that remain unclear and often yield unsatisfactory results. Herein, we characterized the composition and metabolic function of the gut microbiota of patients with MDD during antidepressant treatment, based on 16S rRNA sequencing and metabolomics. The microbial signatures at baseline differed significantly between responder and non-responder groups. The gut microbiota of the non-responder group was mainly characterized by increased relative abundances of the phylum Actinobacteria, families Christensenellaceae and Eggerthellaceae, and genera Adlercreutzia and Christensenellaceae R7 group compared to that of the responder group. Additionally, the gut microbiota composition of the responder and non-responder groups differed significantly before and after treatment, especially at the genus level. Moreover, 20 differential metabolites between the responder and non-responder groups were identified that were mainly involved in lipid metabolism (cholestane steroids and steroid esters). Eggerthellaceae and Adlercreutzia displayed strong co-occurrence relationships with certain metabolites, suggesting alternations in the gut microbiome, and associated metabolites may be potential mediators of successful antidepressant treatment. Overall, our study demonstrates that alterations in gut microbiota composition and metabolic function might be relevant to the response to antidepressants, thereby providing insight into mechanisms responsible for their efficacy.